Peningkatan Pemahaman Siswa SD dalam Mengenal Pecahan Senilai Melalui Tutor Sebaya di Kelas IV - Melly Wardani Pratiwi; Felycia Rusfadia Sari; Imam Gazali Bahtiar; Sofiatul Fitria (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2025)
This research aims to increase fourth grade elementary school students’ understanding of the concept of equivalent fractions through peer tutoring. The research was conducted at SDN Ponteh 1, Galis District, Pamekasan Regency, using the Classroom Action Research (PTK) approach which consists of planning, implementing, observing and reflecting. The peer tutoring method allows students who are superior in understanding the material to help their friends who are experiencing difficulties. The research result showed that this method was effective in increasing students’ understanding, with 100% of students succeeding in achieving learning mastery in this first cycle. The application of the peer tutoring method makes it easier for students to understand the material because of the simple and relevant delivery from their peers. These findings indicate that the peer tutoring method can be an effective solution in learning mathematics, especially equivalent fraction material at the elementary school level